ANALYSIS OF COASTLINE CHANGES IN GORONTALO CITY USING REMOTE SENSING TECHNOLOGY - Mahua, Musdalifah; Kasim, Faizal; Pasisingi, Nuralim (Jurnal Ilmu Kelautan SPERMONDE, 2023)
Coastal areas are important for economic activities, but are also vulnerable to environmental changes caused by human activities. The use of remote sensing technology can assist in efficient and accurate monitoring of coastline changes related to the spatial-temporal dynamics of coastlines in local areas, which is needed in the development of effective coastal management strategies. By applying the Modified Normalized Difference Water Index (MNDWI) method for coastline extraction, the research results show that the addition of coastal areas (accretion) as a dominant process in coastal stability in almost all coastal areas of Gorontalo City during the period 2000-2022, has experienced the significantly accelerated trend during the 2015-2022 period with an increase in the accretion rate of 60.15%. The rate of accretion in this period has caused an increase in the land area of coastal areas by 425.44% compared to the accretion that occurred during the 2000-2015 period. The findings of this research can be used as a basis for further research regarding the impact of human activities on coastal ecosystems and the effectiveness of Gorontalo City's coastal management strategies.